Integrated Assessment in Drugs Crimes as Efforts to Prevent Drugs Abuse in Indonesia - et al., Yusuf Saefudin (International Journal of Advanced Science and Technology, 2019)
This paper aims to examine the mechanism of Integrated Assessment in Indonesian drugs crimes. Also intends to explore whether the Integrated Assessment as a new paradigm is able to reduce the number of drug demand (demand reduction) or not. Given that globalization has a tremendous impact on the development of science and technology. One of the impacts is an increase in transnational drugs crimes along with the growing sophistication of technology. The research method used in this study is normative juridical, with a statute approach, conceptual approach, and historical approach. The specification of this research is descriptive research. Data sourced from primary legal materials and secondary legal materials obtained were analyzed using qualitative analysis. The results of the study show that an integrated assessment is a mechanism that is formed based on joint regulations to place addicts and drugs abusers into medical/ social rehabilitation institutions. Integrated assessment provides a great opportunity for drug addicts and drug abusers to be rehabilitated. Rehabilitation is one way to reduce the number of requests for drugs (demand reduction) which will have implications for reducing the number of illicit drug trafficking in Indonesia.